Use of a liquid nicotine delivery product to promote smoking cessation - Kepner James L; Baumgarten Deborah; Olson Carl E; Geimer Nicholas; Mahoney Martin C (BMC, 2010)
Abstract Background Despite access to various pharmacotherapies and counseling support to aid cessation, smokers typically demonstrate quit rates below 50%. This report describes the results of a Phase 2a study exploring the efficacy of a liquid nicotine delivery system as an aid to smoking cessation assessed after 12 weeks of therapy. Methods A single-arm Phase 2a study was conducted. Community-based smokers (ages 18+ years, smoking at least 10 cigarettes daily for the past year and interested in making a quit attempt) were recruited and completed clinic visits at 2 week intervals over the 12 week study period where carbon monoxide levels were assessed and the Smoke-Break product was rated on taste and overall satisfaction. Participants were provided with a supply of liquid nicotine cigarettes (e.g., Smoke-Break) at each clinic visit. A total of 69 smokers were enrolled and received the intervention product (intention to treat group, ITT) and 52 smokers verified participation (according to protocol group, ATP). Results The cessation rate at 12 weeks after the baseline visit, assessed as the bioverified point prevalence of abstinence, was 71.1% (95% confidence interval [CI] 58.8%-83.5%) in the ATP group and 53.6% (41.8%-65.4%) in the ITT group. Participants rated the liquid nicotine delivery system highly and also expressed general satisfaction. Few adverse events were identified with no serious adverse events. Conclusions These results support the efficacy of the liquid nicotine delivery system in smoking cessation. If this nicotine delivery product proves to be effective in larger trials, it could represent an inexpensive, readily accessible and well-tolerated agent to promote smoking cessation. Trial Registration This trial is registered at clinicaltrials.gov as study NCT00715871.